2007
DOI: 10.1073/pnas.0608584104
|View full text |Cite
|
Sign up to set email alerts
|

Protein-induced, previously unidentified twin form of calcite

Abstract: Using single-crystal x-ray diffraction, we found a formerly unknown twin form in calcite crystals grown from solution to which a mollusc shell-derived 17-kDa protein, Caspartin, was added. This intracrystalline protein was extracted from the calcitic prisms of the Pinna nobilis shells. The observed twin form is characterized by the twinning plane of the (108)-type, which is in addition to the known four twin laws of calcite identified during 150 years of investigations. The established twin forms in calcite ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 20 publications
7
51
0
Order By: Relevance
“…The lattice parameters of synthetic calcite calculated from the XRD patterns were found to be as follows: a = 4.988 Å and c = 17.08 Å; these values are in good agreement with the literature values for rhombohedral symmetry (in hexagonal axes): a = 4.991 Å and c = 17.061 Å. 32 The interplanar angle between the (001) and (104) planes calculated by using a general equation 36 based on the experimental data was found to be approximately 44.61 o . By using this value, we performed crystallographic analysis of the fabricated calcite crystals by following a previously reported method.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The lattice parameters of synthetic calcite calculated from the XRD patterns were found to be as follows: a = 4.988 Å and c = 17.08 Å; these values are in good agreement with the literature values for rhombohedral symmetry (in hexagonal axes): a = 4.991 Å and c = 17.061 Å. 32 The interplanar angle between the (001) and (104) planes calculated by using a general equation 36 based on the experimental data was found to be approximately 44.61 o . By using this value, we performed crystallographic analysis of the fabricated calcite crystals by following a previously reported method.…”
Section: Resultssupporting
confidence: 75%
“…As shown in Figure 1(a), many of the particles had cleavage faces of (104) orientation, which is a well-known crystallographic orientation in calcite and also the most thermodynamically stable face. [32][33][34] From the XRD result, however, diffraction peaks of the vaterite phase (ICSD card no: 33-0268) appeared following addition of 5 mg/mL PASP, and diffraction intensity of the calcite phase decreased, as shown in Figure 2(b). Along with the increase in PASP concentration, the gradual disappearance of diffraction peaks of calcite, along with a gradual increase of vaterite, can be seen in Figure 2(c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By definition, a twin plane results from a combination of particular crystallographic orientations in adjacent sectors and a particular orientation of the interface plane. This is illustrated with the theoretical case of the calcite twin (104), which is an established twin plane of calcite (Pokroy et al 2007). The atomic orientation of the calcite twin (104) with two adjacent sectors (blue and pink) is shown in Figure 5e.…”
Section: Interpretation Of the Sectored Sclerites: Twinning Or "Mesotmentioning
confidence: 97%
“…Pokroy et al (2007) reported their discovery of a formerly unknown twin form in calcite crystals grown from solution to which a mollusc shell-derived 17-kDa protein, Caspartin, was added. This intracrystalline protein was extracted from the calcitic prisms of Pinna nobilis.…”
Section: Discussionmentioning
confidence: 99%